2018
DOI: 10.1088/1361-6560/aaa1c9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of stopping-power prediction from single- and dual-energy computed tomography in biological tissues

Abstract: Abstract. An experimental setup for consecutive measurement of ion and x-ray absorption in tissue or other materials is introduced. With this setup using a 3D-printed sample container, the reference stopping-power ratio (SPR) of materials can be measured with an uncertainty of below 0.1%. A total of 65 porcine and bovine tissue samples were prepared for measurement, comprising five samples each of 13 tissue types representing about 80% of the total body mass (three different muscle and fatty tissues, liver, ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 26 publications
4
69
2
Order By: Relevance
“…If the additional uncertainty due to noise at a 2% noise level for a tumor at 5 cm depth (a worst case scenario) is considered, the total uncertainty becomes 2.52% and 4.10% for the soft and bone tissue group, respectively, which is only a marginal increase of 0.12% and 0.10%. However, a few recent experimental validation studies using DECT reported the overall range uncertainty to be around 1% or less . If 1% were assumed as the range uncertainty for both the soft and bone tissue groups, the total uncertainty after including the noise becomes 1.52% and 1.37% for the soft and bone tissue group, respectively, which is a decent increase of 0.52% and 0.37%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the additional uncertainty due to noise at a 2% noise level for a tumor at 5 cm depth (a worst case scenario) is considered, the total uncertainty becomes 2.52% and 4.10% for the soft and bone tissue group, respectively, which is only a marginal increase of 0.12% and 0.10%. However, a few recent experimental validation studies using DECT reported the overall range uncertainty to be around 1% or less . If 1% were assumed as the range uncertainty for both the soft and bone tissue groups, the total uncertainty after including the noise becomes 1.52% and 1.37% for the soft and bone tissue group, respectively, which is a decent increase of 0.52% and 0.37%.…”
Section: Discussionmentioning
confidence: 99%
“…Dual‐energy CT (DECT)‐based approaches have demonstrated their capability of reducing this uncertainty as well as their clinical applicability and relevance to the patient . Various methods have been proposed that estimate proton SPR using two or more CT numbers acquired from different energy spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data are under acquisition by our research group and will be disclosed in future publications. However, data on experimental verifications of SPR predictions with DECT have been recently reported . In all three studies, animal tissue samples were used.…”
Section: Discussionmentioning
confidence: 99%
“…These studies include investigations on how to perform a robust calibration of the conversion from CT numbers in conventional single‐energy CT (SECT) to SPR, the influence of beam hardening (BH), the use of dual‐energy CT (DECT), as well as the use of proton CT . It has been shown in several studies that DECT gives more accurate SPR estimates than SECT using the stoichiometric method proposed by Schneider et al …”
Section: Introductionmentioning
confidence: 99%